KEBERSIHAN (Hygiene) MAKANAN DAN SANITASI DI RUMAH MAKAN KAMPUS - Mercy A. Lumare; Irza N. Ranti (POLTEKKES KEMENKES MANADO, 2016)
Cleanliness (Hygiene) and sanitation of food processing at home eating is important to notefrom selecting raw materials to be processed foods until the presentation. Since this greatlyaffects the sustainability of the various needs of the body in meeting survival.Implementation Hygine and Sanitation in food processing is often overlooked due tonegligence, which in turn adversely affected the humans who consume them.A chef plays an important role in various processes of early elections to the presentation offoodstuffs, thus these things must be fulfilled as a condition of the food standards which areclean so that the consumer nor the service all the guests were satisfied